Observatório Social de Maringá - PR : uma ferramenta eficiente de accountability junto aos poderes executivo e legislativo do município? - Capelette, Marcia Clotilde Facci (2016)
Draws attention of the academic world the growing implementation of institutions wich purpose is to monitorize the municipal public administration, institutions commonly called citizens or social observatories. This fact has led many researchers around the world to discuss the effectiveness of similar systems, recently adopted in several countries, including Brazil. Between 1999 and 2015 about 100 Social Observatories were implemented in Brazil, one of them is the Maringá Social Observatory. Some facts, besides the growth of similar institutions around the world, justify our choice for researching about OSM, wich are: it is one of the first institutions of its kind officialized in Brazil; it operates in the third largest city in Paraná State, historically known for being an elitist city, and that has many social and political problems. The methodology used was qualitative research. The questions we set out to answer are: Would the OSM be an effective accountability tool up the executive and legislative branches of Maringa city? Would the savings from the municipal treasury generating other benefits to the population? Educational activities are geting cultural change with regard to public administration? Our first assumption is that the OSM, despite the paltry financial and human resources, and even not reaching a number that could be considered ideal of monitored bids, has made a work never before done in the municipality, developing activities that exceed those concerned to the agencies responsible control, generating considerable savings to the public coffers. In reference of being the OSM one representative body of civil society, its initial constitution shows that this statement is not possible, according to the studies of Izunza Vera and Gurza Lavalle (2012). On the other hand, the opening for the participation of society in his board leads us to affirm that the OSM does not bring, at its core, the intention to represent this or that social sector. The requirement of non-partisan link, such a premise by itself, does not guarantee isonomy in decision-making. However, na OSM differential detected during our research, is that its actions involved awareness and training people, which put it in a prominent place among the observatories of which we have news. We can also say that actions wich aimed cultural changes as those developed by OSM have no effect in a short or even medium deadline, but long term, what we understand as possible fact condicioneted to the continuity institution operation.